Application of the Weighted Product Method and Simple Multi-Attribute Rating Technique (SMART) for Selecting Recipients of the Family Hope Program (PKH) - Wardhani, Indah Kusuma; Triyanto, Wiwit Agus; Supriyono, Supriyono (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The Family Hope Program (PKH) is a social assistance initiative aimed at improving the welfare of underprivileged families through conditional cash transfers. In the selection process for recipients, this study directly compares two Decision Support System methods: the Weighted Product method and the Simple Multi-Attribute Rating Technique (SMART). These methods employ different calculation approaches; the Weighted Product method uses multiplication, where higher weights have a greater influence on ranking, while the SMART method utilizes linear addition after normalization, which can affect the ranking results. Previous studies generally used only one method or compared similar methods. The criteria used include welfare indicators aligned with the Family Hope Program (PKH), making the results more relevant for decision-making in the context of social assistance. These indicators include pregnant women, the number of toddlers, the number of elementary school children, the number of middle school children, the number of high school children, employment status, income, and housing conditions. The results indicate that both methods yield the same ranking order, although there are differences in the final scores. From 20 alternative data points, five residents of Bugel Village were identified as the most eligible to receive PKH assistance: SH, ZD, SF, SU, and HP.